Experimental poisoning by Baccharis coridifolia in cattle - Tokarnia, Carlos Hubinger; Döbereiner, Jürgen (Pesquisa Agropecuaria Brasileira, 2014)
Baccharis coridifolia (Compositae) is a common and important poisonous plant to livestock in southern Brazil and neighbouring countries. Regardless, there are few data available based on experimentation on its toxicity to cattle. The upper aerial parts of fresh green and of dried B. coridifolia were given orally, in different amounts and at different periods of the year, to 31 bovines. In some animals the doses were repeated. Animals were fed with the plant in regions where it does and does not occur. The plant used in the experiments was collected in Cacequi, Itaqui and Uruguaiana counties, in the State of Rio Grande do Sul. There was great variation in the toxicity of B. coridifolia throughout the year. In October/November, when the plant is sprouting, 2 g/kg were necessary to cause death in the bovines. In March, when the plant is flowering and seeding, 0.25 to 0.5 g/kg were sufficient. This means that the plant in March is 4 to 8 times more toxic than in October/November. The clinical signs, in the cases where the animals died, were anorexia, slight to moderate bloat, swaying gait, sometimes muscular tremors, restlesness, lying down and getting up repeatedly. With time, the animals remained more and more in sternal decubitus, and often tumbled onto their sides. Other signs were dry muzzle, bleary eyes, rumen without rythmic movements and only with a continuous murmur at auscultation, few dry faeces, slight salivation, polydipsia, polypnoea with arrythmia, groaning, tachycardia, and finally the animals laid down on their sides and died in this position within 15 to 60 minutes. The symptoms were quite similar in all the experiments, but in those using the dried plant, bloat and nervous symptoms were not observed. In experiments with the green, fresh plant, bloat occurred more frequently and was more intensive in October/November, whilst nervous symptoms were more noticeable in March. Fresh, green plant material produced first signs of poisoning between 5 and 29 hours after its administration and the symptoms lasted from 4 to 34 hours. The animals died from 14 to 41 hours after ingestion. Dried plant material produced first signs of poisoning 6 to 17 hours after administration and the symptoms lasted from 8 to 63 hours. The animals died between 25 and 74 hours after eating the dried plant. Constipation was generally followed by diarrhoea and loss in weight in experiments which produced no fatality; the illness lasted up to 14 days, after which time rumen movements and appetite were normal again. No differences in susceptibility to poisoning by B. coridifolia was observed between animals from regions where the plant does and does not grow. The dried plant remained toxic for at least 18 months alter its collection storing at room temperature. Approximately half its toxicity was lost during the drying process. In experiments where the plant was administered repeatedly no cumulative effect was revealed, but a little tolerance probably developed. Post-mortem examinations revealed congestion of the mucosa of the rumen and reticulum with oedema of the wall; congestion and petechiae on the mucosa of the abomasum and small intestine, the latter having liquid contents. The liver was lighter in colour than usual. There were hemorrhages on the epicard and endocard. The main histopathological findings were necrosis and detachment of the epithelium of the mucosa of the rumen and reticulum, which was oedemic, congestion in the spleen and oedema of Disse's spaces in the liver.